2015
DOI: 10.1016/j.calphad.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

General method for incorporating CALPHAD free energies of mixing into phase field models: Application to the α-zirconium/δ-hydride system

Abstract: This paper presents a general method of incorporating CALPHAD-based free energies into a phase field model. While CALPHAD-based free energy descriptions provide realistic energetics of alloys, their formulations may pose numerical difficulties for phase field simulations. Specifically, the free energies of mixing for different phases may not necessarily be defined over the same concentration ranges, and their derivatives may exhibit highly nonlinear behavior. The method presented approximates the free energies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…4 gives an overview of the most common coupling approaches. [13][14][15][16][18][19][20][22][23][24][25][26] The methods using direct implementation of the CALPHAD Gibbs free energy expressions (b) or an interface with a thermodynamic software (d), give an exact and continuous representation of the composition dependence of the CALPHAD Gibbs free energies. They are considered as a reference against which the accuracy of the simulations using TTMs is evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 gives an overview of the most common coupling approaches. [13][14][15][16][18][19][20][22][23][24][25][26] The methods using direct implementation of the CALPHAD Gibbs free energy expressions (b) or an interface with a thermodynamic software (d), give an exact and continuous representation of the composition dependence of the CALPHAD Gibbs free energies. They are considered as a reference against which the accuracy of the simulations using TTMs is evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] Different approaches have been proposed to include the CALPHAD thermodynamic descriptions in PFM. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] A classification and discussion of the different approaches is given further in the paper. However, to date, only a few results for quaternary or higher-order systems are reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…To provide example solutions to the benchmark problems, the MOOSE computational framework is used. MOOSE [61,62] is an open-source finite element framework and is the basis for several other phase field applications, including Marmot [33] and Hyrax [63,64]. To avoid computationally expensive fourth-order derivative operators, the Cahn-Hilliard equation is split into the two second-order equations [33,56], given by…”
Section: Methodsmentioning
confidence: 99%
“…We note that, in the phase field community, methods have been recently reported that eliminate such characteristics while largely retaining the free energy values. 80 Hecht et al have reviewed the advances in phase field modeling of multiphase solidification. 81 Other reviews 82,83 and research articles, 84,85 as well as references therein, provide additional examples of how PF modeling and other theoretical methods can be used to understand the physical mechanisms controlling the microstructural development.…”
Section: B Outlook For Computational Studiesmentioning
confidence: 99%